Structural classification of lexical bundles in Indonesian EFL textbooks for senior high school: A corpus-based study - Garini, Selza Azzahra; Oktavianti, Ikmi Nur (Englisia Journal, 2025)
Lexical bundles are fundamental to fostering language fluency and facilitating proficient academic writing, particularly within English as a Foreign Language (EFL) context. However, their prevalence and pedagogical utility in Indonesian EFL textbooks at the secondary level remain underexplored. This study examines the deployment of three-word lexical bundles in Indonesian senior high school EFL textbooks (grades 10–12) aligned with the Kurikulum Merdeka. Adopting a corpus-based methodology, the research employs AntConc software to analyze the frequency, structural composition, and functional distribution of identified bundles. The corpus consists of texts drawn from officially sanctioned textbooks corresponding to the new curriculum. Analysis revealed 53 distinct lexical bundles across the three grade levels. Structurally, noun phrase (NP)-based bundles predominated, followed by verb phrase (VP)-based and prepositional phrase (PP)-based bundles. These findings indicate a deliberate, graded progression in the linguistic complexity of the textbooks, which appears designed to scaffold the development of students’ academic language proficiency. This research contributes to a deeper understanding of lexical bundle integration in EFL instructional materials, underscores their pedagogical significance, and provides insights for future curriculum development and language teaching methodologies.